Pengaruh Sistem Pengendalian Internal, Pemanfaatan Teknologi Informasi, Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Ubud - Agastya, Pande Putu Yogi; Pratiwi, Ni Putu Trisna Windika (UNHI Press, 2025)
Accountability is an important performance control in organizations, including village governments, which must be accountable for their actions to the community to demonstrate good governance. The factors that influence accountability are the Internal Control System, Utilization of Information Technology, and Community Participation. This research aims to determine the influence of the Internal Control System, Use of Information Technology, and Community Participation on the Accountability of Village Fund Management in Villages in Ubud District. The population used in this research was 56 village officials in Ubud sub- district. The number of samples in this study was 56 financial reports which were determined using purposive sampling techniques and tested using multiple linear regression analysis techniques. The results of this research indicate that the Internal Control System has a positive effect on Village Fund Management Accountability. The use of Information Technology has a positive effect on Village Fund Management Accountability. Community Participation has a positive effect on Village Fund Management Accountability.